Innovative Gurus: Tradition and Change in Contemporary Hinduism. - Lucia, Amanda (International Journal of Hindu Studies, 2014)
The article focuses on Hindu ideologies and practices. Discussed are concepts of modern guru movements, characteristics of Hinduism as a religion in India, its public representations and on the functionalist definition of the tradition. Explored are sources of dharma in the Hindu contextualism and concept of bhakti.